2008
DOI: 10.1002/path.2313
|View full text |Cite
|
Sign up to set email alerts
|

Haem oxygenase‐1 regulates catabolic and anabolic processes in osteoarthritic chondrocytes

Abstract: Pro-inflammatory cytokines, matrix metalloproteinases (MMPs) and other catabolic factors participate in the pathogenesis of cartilage damage in osteoarthritis (OA). Pro-inflammatory cytokines such as interleukin-1beta (IL-1beta) mediate cartilage degradation and might be involved in the progression of OA. Previously, we found that haem oxygenase-1 (HO-1) is down-regulated by pro-inflammatory cytokines and up-regulated by IL-10 in OA chondrocytes. The aim of this study was to determine whether HO-1 can modify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 39 publications
7
49
0
Order By: Relevance
“…Although the reduction in heme availability may result in COX-2 protein possessing a low activity, our recent data [41] suggest that a product of HO-1 activity such as CO may be responsible for the reductions in PGE 2 production after HO-1 induction. Our results Recently, we have reported that HO-1 protects against cartilage degradation through the inhibition of the expression of several matrix metalloproteinases [20]. Here, we show for the first time a regulatory role of HO-1 in PGE 2 production due to mPGES-1 modulation, in primary OA chondrocytes stimulated with IL-1, which may participate in the observed protective effects on cartilage.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…Although the reduction in heme availability may result in COX-2 protein possessing a low activity, our recent data [41] suggest that a product of HO-1 activity such as CO may be responsible for the reductions in PGE 2 production after HO-1 induction. Our results Recently, we have reported that HO-1 protects against cartilage degradation through the inhibition of the expression of several matrix metalloproteinases [20]. Here, we show for the first time a regulatory role of HO-1 in PGE 2 production due to mPGES-1 modulation, in primary OA chondrocytes stimulated with IL-1, which may participate in the observed protective effects on cartilage.…”
Section: Discussionsupporting
confidence: 72%
“…Our data suggest that the inhibitory effects of HO-1 induction on the first transcription factor could play a role in the recently reported inhibition of MMP expresion [20]. Although the COX-2 promoter contains multiple regulatory sites including those able to interact with both transcription factors, it has been reported that COX-2 induction by IL-1 in human chondrocytes may be dependent on other transcription factors [44], which would be consistent with the lack of effect of CoPP on COX-2 expression.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations